STRATEGI PENGEMBANGAN KOLEKSI PERPUSTAKAAN STIE SBI YOGYAKARTA DALAM MENDUKUNG KEBUTUHAN PENDIDIKAN DAN PENELITIAN - Dewi, Shinta; Zain, Labibah (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
Collection development is responsible for organizing and expanding collections in libraries. The main purpose of developing collections in university libraries is to meet the information needs of the academic community in higher education. This allowed the library to develop its collection in a planned manner. STIE SBI Yogyakarta Library, as a private university library, acts as an information institution to support the implementation of Tri Dharma of Higher Education. To meet the information needs of users, the library must conduct collection development and formulate policies related to collection development. This research explores the stages of the collection development process at the STIE SBI Library and provides suggestions regarding collection development policies. This study uses a qualitative method with a descriptive approach. Data were collected through observations, interviews, and literature review. The results showed that the stages in the collection development process at the STIE SBI Yogyakarta Library are simple and have not been supported by a written collection development policy. In addition, other obstacles faced by the library include the limited number of librarians and budget. This condition is an obstacle in the implementation of collection development activities.